2002
DOI: 10.1007/s00268-001-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival of patients with stage IV hypopharyngeal cancer: Impact of fundus rotation gastroplasty

Abstract: Abstract. Stage IV circular hypopharyngeai cancer is a disease with poor long-term survival, and the only means of cure---surgery~is associated with high morbidity. All patients admitted with circular hypopharyngeal cancer and extension to the esophagus were enrolled in a multidisciplinary treatment protocol, including circular laryngopharyngoesophagectomy with tracheostomy, neck dissection, and pull-up of a fundus rotation gastric tube that was anastomosed to the oropharynx. Five weeks postoperatively high-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…These data are rarely reported in the literature, but Oniscu et al [22] reported satisfactory swallowing of 78% after 6 months and 81% after 12 months, suggesting that a rehabilitation period of 2 months should on average be expected. An interesting alternative reconstruction technique was introduced by Schilling et al [23] who described the use of a fundus rotation gastroplasty resulting in a low complication rate and moderate dysphagia during the first 6 months after surgery which resolved within 1 year. Patients undergoing total laryngopharyngectomy are generally patients with advanced disease, roughly 75% having stages III or IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…These data are rarely reported in the literature, but Oniscu et al [22] reported satisfactory swallowing of 78% after 6 months and 81% after 12 months, suggesting that a rehabilitation period of 2 months should on average be expected. An interesting alternative reconstruction technique was introduced by Schilling et al [23] who described the use of a fundus rotation gastroplasty resulting in a low complication rate and moderate dysphagia during the first 6 months after surgery which resolved within 1 year. Patients undergoing total laryngopharyngectomy are generally patients with advanced disease, roughly 75% having stages III or IV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Using preoperative radiotherapy followed by a similar surgical technique as in the present study, Oniscu et al [12] found a 1- and 3-year survival of 52 and 33% respectively in 20 consecutive patients with hypopharyngeal carcinoma. In addition, Shilling et al [9] recently reported a 3- and 5-year survival of 72 and 60% respectively after surgical resection, fundus rotation gastroplasty and early postoperative radiation in 18 patients with hypopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Two-stage operations such as the deltopectoral flap technique, colon interposition, reversed gastric tubes, local and regional skin flaps have to a large extent been replaced by one-stage procedures such as gastric pull-up or reconstruction with free fasciocutaneus microvascular transplants [2,3,4,5,6,7,8,9,10,11]. The use of free jejunal transplants has been popularized during the last decades and advocated by many surgeons [12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Grundlage dieser Untersuchung war die publizierte exorbitant gute Überlebensrate (60%) nach Laryngoöso-phagektomien mit konsekutiver Magenhochzugs-Op. bei T4b-Hypopharynxkarzinomen [46]. Erfahrungsgemäß ist die 5-Jahres-Überlebensrate dieser Tumoren < 25% und konnte durch die konsequente Entfernung des gesamten Öso-phagus deutlich verbessert werden.…”
Section: Plattenepithelkarzinome Des Kopf-hals-bereichsunclassified